PARENTING: METODE PEMBENTUKAN KARAKTER ISLAM PADA ANAK USIA DINI DI KOTA PALANGKA RAYA (Studi Kasus 3 Keluarga Islam) - Syarifah Bidasari (Prodi Sosiologi FISIP UPR, 2019)
As the function of the family is as the first school for their children and parents have an obligation to introduce, invite and instill religious values to their family members. Children are given the opportunity to develop their religious knowledge in daily life through activities that they have. The family also has a role in addition to being a mentor and educator, he is also a supervisor or companion for his children in his infancy. The problem in this study is how parenting is given by the family to the development of the Islamic character of children at an early age in Palangka Raya using the Parenting method. The results of this study can be used as reference material to provide an overview of children's education using method parenting. This research is a study that uses qualitative methods by holding observations and interviews analyzed by reducing data and presenting data from the results of interviews or observations. The results of this research show from the pattern of parenting parents who provide education to children. In educating children, parents need education related to the science of educating children, where each child has his own character. First, reading culture is one way for these three families to set an example for children. Second, the example given by parents to children is an easily accepted method by children, where when the child is at an early age is still in the development phase. Third, the rules agreed upon in the family and the assertiveness that parents have in implementing the rules are important when the family wants to build a disciplined attitude in children.